Unusual Presentation of Oral Squamous Cell Carcinoma in a Young Woman - Diurianne CC França; Lira M Monti; Alvimar L de Castro; Ana MP Soubhia; Luiz ER Volpato; Sandra MHC Á de Aguiar; Marcelo C Goiato (Sultan Qaboos University Medical Journal, 2012)
Oral squamous cell carcinoma (OSCC) is the most common oral malignant neoplasm, mainly affecting individuals over 50 years old with a history of tobacco and alcohol use. The occurrence of this oral cancer in individuals under 40 years old is unusual and, when it does occur, shows a weaker relation to those risk factors and a more aggressive clinical course. Due to the paucity of reports in this population, it is difficult to prove its increasing trend. A case of oral squamous cell carcinoma in a 39-year-old woman with no history of tobacco or alcohol use is reported. Clinical and histopathological findings, aetiology, and treatment are discussed. The increasing trend of oral squamous cell carcinoma in young women without known risk factors highlights the need for clinicians to be prepared to diagnose this lesion quickly and precisely, providing a better prognosis, chance of survival, and quality of life for the patient.